Investigation of the Ion Energy Transport in the Scrape-Off Layer on the J-TEXT Tokamak Using a Retarding Field Analyzer - 刘海 陈志鹏 庄革 孙岳 朱立志 肖持进 陈杰 (Plasma science & technology, 2016)
Radial profiles of the ion temperature,Ti,have been measured by a double-sided retarding field analyzer（RFA） in the scrape-off layer（SOL） of the J-TEXT tokamak（R = 105 cm,r = 25-29 cm,Bt = 1.8-2.0 T,Ip = 120-180 kA,ne =（2-2.5） × 10^19 m^-3）.Strongly declining Ti profiles in the SOL have been found.The different e-folding lengths,At,of the Ti profiles in two experimental configurations with different magnetic connection lengths,Lc,reveal that a longer Lc results in weaker parallel energy transport and longer At.In similarity with the particle transport across the SOL,At is approximately proportional to the square root of Lc.Additionally,the poloidal asymmetry has been identified with enhanced ion energy transport across the SOL on the low-field side.